Sexo, mercadoria e hábitos de consumo em HQ: comunicação, empreendedorismo e gestão de si como produto. - Setyon, Clarisse (2011)
Considering that media culture is also consumer culture, communication and consumption feature as fundamental social practices in today´s world. Analyzing the strong presence of themes related to sexuality in the current media production, a scenario, here named the mercantilization of the sexual sphere, is unveiled. This scenario has post-modernity and the society of the spectacle as its background. This is the social environment where autonomous individuals, in search of the so-called security, are eagerly looking not only for rules and behavior models, but also for the ongoing improvement of their subjectivities. This is necessary in order to reach a stand out position in relation to their peer groups. It is visible, today, the proliferation of a large collection of products, services and abilities related to what we are here defining as consumption practices in the arena of sexual relations. Many are the media speeches which have been supporting this type of mercantilization, rendering practices and object s into products and services available in the retail market. In this present study, we have examined advertising campaigns and TV programs which deal with contemporary sexuality. More specifically, this work aims to examine the speech provided through the cartoons of Adão Iturrusgarai, published in the largest Brazilian daily newspaper. From the large and varied production of this author, we have selected a series of comic strips, which, we believe, function as an acid social criticism of the contemporary sexuality in the language of the cartoons.